Micropatterning in Cell Biology. - Piel, Matthieu; Thery, Manuel (Methods in cell biology, 2014)
"Micropatterning refers generally to techniques which provide an experimental control over the chemical, physical, or geometrical properties of materials at the micron or submicron scale, and are thus used to produce spatial patterns of these properties. These techniques, which were often originally designed for application in microelectronics, have spread over most areas of science, including biology. They have proved particularly useful for cell biology, bridging the gap between the Petri-dish and complex 3D assays and tissues."--Preface.